Experiences of Parents as Para-Teachers to their Elementary Children - Salindato Jr, Joel P; Gomez, Aurelio Jr., S. (Journal of Social Work and Science Education, 2024)
This study aimed to describe the experiences of parents as para-teachers of their child’s education at home that would serve as basis to improve the delivery of primary education instruction. The participants were the ten parents of learners enrolled in a public elementary school, utilizing exploratory case study design to explore the experiences of the parents. A semi- structured interview guide was used to gather the data. Ethical considerations were observed in data collection. The themes were extracted using thematic content analysis. The findings were: time constraint, inattentive child, and unskillful parents are the challenges encountered by the participants; their coping mechanisms with the challenges encountered are strong partnerships are established, discipline is strongly implemented, different types of motivation are applied, initiative disposition is developed, and personal attributes are amplified; and strengthening of stakeholders’ partnership, capacitating parent’s basic instructional skills, and improving parental behavior management strategies are the insights derived from the experiences of the parents.